Effect of Isometric Handgrip Exercise on Blood Pressure Reduction in Individuals with Prehypertension and Stage 1 Hypertension - Marescha Alehandro L. Pajukang; Su Djie To Rante; Regina Marvina Hutasoit; Deif Tunggal (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Hypertension is a significant worldwide health concern that greatly affects heart-related illnesses and deaths. One recommended method to help lower blood pressure without medication is the isometric handgrip exercise. This research aimed to investigate the impact of isometric handgrip exercise on lowering blood pressure in those with prehypertension and stage 1 hypertension. The study utilized a quasi-experimental design following a two-group pretest–posttest format. The participants included 50 seminarians from Seminari Tinggi St. Mikhael Penfui, Kupang, who were chosen through purposive sampling based on specific inclusion and exclusion criteria. The participants were split into two groups: the intervention group (n = 25) that engaged in isometric handgrip exercises for three minutes daily over five days, and the control group (n = 25) that did not participate in any exercise. The data were evaluated using the Wilcoxon Signed Rank test and the Mann–Whitney test. After five days of exercise, a notable decrease in blood pressure occurred in the intervention group, both for prehypertension (systolic p < 0.001; diastolic p = 0.005) and stage 1 hypertension (systolic p = 0.003; diastolic p = 0.012). No remarkable changes were noted in the control group (p > 0.05). The comparison between the two groups indicated significant differences in blood pressure changes for both categories (p < 0.05). Isometric handgrip training significantly affects reducing blood pressure in individuals with prehypertension and stage one hypertension.